Compilation and standardization of oil toxicity data on early life stages of fish to support population-level oil spill impact modeling - Vikkula, Sami; Mäntyniemi, Samu; Kuikka, Sakari (Elsevier, 2025)
The risk of oil spills has increased in recent years due to rising tanker traffic and the emergence of poorly maintained vessels. While the environmental impacts of oil spills are wide-ranging, their effects on fish populations remain contested, prompting the need for further research and the development of improved tools and methodologies for impact assessment. One complicating factor is the heterogeneity of existing laboratory exposure data, which hinders their usage in population-level oil spill impact assessment. This study addresses that gap by compiling a dataset from peer-reviewed laboratory exposure studies on the early life stages (ELS) of fish exposed to oil. Through a systematic literature review, we identified relevant studies and developed novel standardization methods to improve data comparability. These methods included converting diverse exposure metrics to a baseline polycyclic aromatic hydrocarbon (PAH) concentration metric, calculating the geometric mean and time-weighted average concentrations, and modeling missing control concentrations. The resulting dataset encompasses multiple fish species and oil types, as well as wide exposure time and PAH concentration ranges, in order to support impact assessments across diverse spill scenarios in fish population dynamics models. Although our methodology significantly increased the amount of usable data, the species and oil type coverage remained uneven, requiring model structures that accommodate information borrowing. We provide recommendations to improve future experimental reporting and suggest methodological extensions for the standardization methods. This study demonstrates how structured data compilation and standardization can cost-effectively expand the applicability of existing experimental data for oil spill impact assessment.
Keywords: oil spills; fisheries; impact assessment; toxicity model; data heterogeneity; polycyclic aromatic hydrocarbons